Konsekwencje "nieprzystawalno?ci" norm pa?stwowego prawa ma??e?skiego do norm ko?cielnego prawa ma??e?skiego - Krzywda, Józef (Rodzina w prawie, 2013)
Consequences of lack of conformity of legal norms from state marriage law to norms from ecclesial marriage law